1966
DOI: 10.1111/j.1365-2141.1966.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosomes in Polycythaemia Vera

Abstract: THERE have been few previous cytogenetic studies of patients with polycythaemia Vera (P.V.). Nowell and Hungerford (1962) and Nowell (1965) investigated the chromosomes of the bone marrow and peripheral blood in five patients with polycythaemia who had been treated with radio-phosphorus ("P). They found abnormal cell lines in four patients, one of whom had developed leukaemia. Kenip, stafford and Tanner (1961) examining the bone marrow by the short-term culture method, found that seven out of nine cases of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Deletion of chromosome 20q, which was originally described in 1966 as an F-group chromosomal deletion in PV, 110 occurs in a range of myeloproliferative disorders. 111 It is a common finding, for example, not only in PV, [53][54][55] but also in PMF [26][27][28]112 and may occur in ET, 114,115 chronic neutrophilic leukaemia, 62 myelodysplastic syndromes 113,114 and acute myeloid leukaemia, 115 although rarely in lymphoproliferative malignancies.…”
Section: Chromosome 20mentioning
confidence: 99%
“…Deletion of chromosome 20q, which was originally described in 1966 as an F-group chromosomal deletion in PV, 110 occurs in a range of myeloproliferative disorders. 111 It is a common finding, for example, not only in PV, [53][54][55] but also in PMF [26][27][28]112 and may occur in ET, 114,115 chronic neutrophilic leukaemia, 62 myelodysplastic syndromes 113,114 and acute myeloid leukaemia, 115 although rarely in lymphoproliferative malignancies.…”
Section: Chromosome 20mentioning
confidence: 99%
“…In 23 cases, including myelodysplastic syndromes (13), myeloproliferative disorders (6), acute myeloid leukemia (2), and autoimmune disorders (2), 20q-occurred with other cytogenetic abnormalities, including del(5q), An interstitial or terminal deletion of the long arm of chromosome 20 (20q-) has been described as a recurring karyotypic abnormality in various types of hematologic disorders. It was first described as an F group chromosome abnormality in bone marrow specimens from patients with polycythemia vera 1 and identified as 20q-by Reeves and colleagues in 1972. 2 Since then, its association with polycythemia vera has been confirmed.…”
mentioning
confidence: 99%
“…There was some indication that the patients with the lowest GPT activities were most likely to show chromosome abnormalities. In four of these patients the abnormal chromosome was a number 20 with a deletion in the long arm (2Oq-) which has a degree of specificity for PRV (Kay et al, 1966;Millard et al, 1968;Lawler et al, 1970;Reeves et a / , 1972) although it has been found in other myeloproliferative disorders (de Grouchy et al, 1966;Nowell et al, 1976). These findings are in accordance with the previous study by Millard et a1 (1968) in which abnormally high levels of the tryptophan metabolites kynurenine, 3-hydroxykynurenine and anthranilic acid, indicating deficiency of B6, were found in the urine of some PRV patients, particularly those with the 20q-abnormality.…”
Section: Discussionmentioning
confidence: 99%